Pengembangan Media Pembelajaran Interaktif Capera Berbasis Canva pada Materi Sistem Pencernaan Manusia Kelas V - Ifadah, Nihayatul; Bektiningsih, Kurniana (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
This research aims to develop and test the feasibility and effectiveness of Capera-based interactive teaching materials for grade V SD on human digestive system material. Research and Development (R&D) is the research method used and the ADDIE model is the development model consisting of analysis, design, development, implementation, and evaluation stages. Observation, interview, questionnaire, pretest, and posttest were conducted to obtain data. The validity test was conducted by two validators, namely material experts and media experts. The percentage score is in the very feasible category with 90,63% for validation from material experts and 90% for validation from media experts. With a percentage score of 96% for students and 100% for teachers, both groups responded well to the learning materials. N-Gain test, paired sample t-test, and normality test were used to assess the effectiveness. Based on the results of data analysis, it was found that 60.93 for the pretest average score then increased to 86.38 in the posttest and 0.6125 was the result of the N-Gain test which was included in the moderate category. The t-test results show a significant difference between the use of Canva-based Capera interactive learning media before and after, with a significance value of 0.000 (<0.05). Thus, it can be said that this learning resource is feasible, valid, and efficient to be used in IPAS learning related to the Human Digestive System.